ANALISIS PERAN STAKEHOLDERS DALAM PENANGGULANGAN BENCANA BANJIR DI KOTA SEMARANG - Rizka Utami Indra; Retna Hanani; , Kismartini , Kismartini (Journal of Public Policy and Management Review, 2023)
Floods are one of the disasters that often occur in Semarang City. In an effort to minimize the occurrence of flood disasters, involvement from stakeholders is needed. This study aims to analyze the role of stakeholders in flood disaster management efforts and analyze the supporting and inhibiting factors of stakeholders' role in flood disaster management in Semarang City. This research method uses a qualitative descriptive approach. Data collection was conducted through interviews and literature studies. The informant determination technique uses purposive sampling techniques. The results of this study show that the Semarang City Regional Disaster Management Agency is a key stakeholders in flood disaster management. Then the residents of Tanjung Mas Village and the Semarang City Public Works Office are the primary stakeholders. Furthermore, the Semarang City Spatial Planning Office, Pemali Juana River Basin Center, and Tanjung Mas Village Government are secondary stakeholders. These stakeholders carry out the role of stakeholders analyzed according to Nugroho's theory in (Setiawan et al., 2018), namely: Policy Creator, Coordinator, Facilitator, Implementer, and Accelerator. Each stakeholders carries out its role in accordance with their respective duties and functions. The supporting factors for the role of stakeholders in flood disaster management, namely: values, beliefs, and policies. While the inhibiting factor of the role of stakeholders is found in communication problems.